STOCK POWER: Uncovering the Effect of Asset Structure, Sales Growth, and Business Risk on Share Prices with the Support of Capital Structure as a Regulator - Ariyanti, Rina (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to determine the effect of Asset Structure, Sales Growth and Business Risk on Stock Prices with Capital Structure as a moderating variable. This type of research is quantitative associative. The sampling method with the